The Effecf Of Locally Generated Revenue And Balancing Funds On The Level Of Regional Financial Independence - Novi DARMAYANTI; Laely Aghe AFRICA; Damayanti DAMAYANTI; Rikah RIKAH (Journal of Tourism Economics and Policy, 2023)
This study aimed to determine the effect of locally generated revenue and balancing funds on the level of regional financial independence partially or simultaneously. The population in this study is the Lamongan District Budget Realization Report in the Office of the Financial Management Agency and Regional Assets (BPKAD). This study used an observation period from 2012-2019, with the saturation sampling method for the past eight years. The data analysis method used in this study is a multiple linear regression test with SPSS. This research used a quantitative approach, which conducted a theory test by measuring the research variables with numbers and analyzing the data using statistical procedures. The variables used are Regional Original Revenue and Balancing Funds as independent variables, with the Regional Financial Independence variable as the dependent variable. The results of this study produced findings that partially, the Original Regional Revenue significantly influences the Regional Financial Independence, and partially the Balancing Fund does not significantly influence the Regional Financial Independence. Whereas simultaneously, Regional Original Revenues and Balancing Funds significantly affect Regional Financial Independence. The contribution of Transfer Revenue (Balanced Fund) to Total Regional Income shows a high figure during the 2012-2019 research period.